Peran Mahkamah Konstitusi dalam Menjamin Hak-Hak Kewarganegaraan di Indonesia - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Ki Awang Pijar Pembayun; Khoridatul Bahiyah; Muhana Ayu Devita (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research explores the role of the Constitutional Court (MK) in protecting citizenship rights in Indonesia. As a constitutional judicial body, the MK holds a crucial responsibility to review laws against the 1945 Constitution (UUD 1945), ensuring that fundamental rights of citizens, such as freedom of expression, the right to education, and the right to privacy, are not violated by existing legal policies. Through the mechanism of judicial review, the MK acts as a primary guardian capable of annulling laws that are in conflict with the constitution. This study examines various significant cases where the MK has played a critical role in safeguarding citizenship rights. We also identify various challenges faced by the MK, including issues in implementing rulings and potential political pressures that may affect the independence of this institution. From a global perspective, this research compares the role of the MK with constitutional bodies in other countries to provide a broader understanding of how the MK functions in an international context. The research employs doctrinal legal research, which is a process of discovering rules, principles, and doctrines to address the issues at hand. The research is prescriptive in nature. The methodology used is normative/doctrinal/library research. The findings indicate that although the MK has successfully protected citizens' rights through significant rulings, there remains an urgent need to improve the implementation of decisions and to safeguard the institution’s independence. Recommendations for enhancing the MK’s role include expanding legal education to the public, strengthening public access to judicial review mechanisms, and fostering closer collaboration with legal academics and practitioners. With these measures, the MK is expected to continue functioning effectively as a guardian of constitutional rights in Indonesia.